Teacher Isolation: How Mentoring Programs Can Help - Kelly L. Heider (Arizona State University, 2015)
Teacher attrition has become a very serious problem in the United States in recent years. Studies have shown that many talented, new teachers are leaving the profession early in their careers due to feelings of isolation. In response to the alarming turnover rate, school districts have adopted mentoring programs which have been successful at making beginning teachers feel less isolated. This article examines four such mentoring programs and their potential to reduce teacher isolation.